CHARACTERISTICS OF PITUITARY-OPVARIAN-ADRENAL AXIS IN ADOLESCENT GIRLS WITH HYPERPROLACTINEMIA OF VARIOUS GENESIS - A. V. Labygina; L. M. Lazareva; L. V. Suturina; L. I. Kolesnikova; L. F. Sholokhov; E. E. Khramova; T. L. Olifirenko; E. S. Shaulskaya (Acta Biomedica Scientifica, 2012)
The article presents the results of examination of 97 adolescent girls (mean age 14,96 ± 0,26 years) with hyperprolactinemia (PRL levels above 700 IU/ml): 30 adolescent girls with pituitary microprolactinoma (mean age 14,7 ± 3.2 years) and 67 adolescent girls with functional hyperprolactinemia (mean age 14,6 ± 3,4 years). The control group included 35 healthy adolescent girls (mean age 15,8 ± 0,89 years). Hyperprolactinemia (tumor and non-neoplastic) in puberty leads to disorders of sexual development and ovarian-menstrual cycle, followed by neurological symptoms. Elevated concentrations of testosterone, cortisol, DHEA, 17-OH-progesterone and LH/FSH ratio were shown in adolescents with hyperprolactinemia compared to the control group. Macroprolactinemia was estimated in 16,4—20 % of girls with hyperprolactinemia.